Chinese pre-service general education teachers’ attitudes and self-efficacy toward inclusive education - Yang, Yi; Liu, Hsi-Wu; Chi, Chao-An; Bak, Moon Young Savana (Frontiers in Psychology, 2025)
In China, full inclusion of students with disabilities in general education classrooms with their same-aged peers is strongly encouraged but not yet legally mandated. As such, the attitudes of general education teachers to include students with disabilities in their classrooms and teacher self-efficacy of inclusive education are two important factors that can decide the success or failure of inclusion. The current study conducted a survey to understand pre-service general education teachers’ attitudes and self-efficacy of inclusive education. We surveyed 587 pre-service general education teachers in the Guangdong province of China using the Sentiment, Attitudes, and Concerns about Inclusive Education-Revised Scale to measure teacher perspectives and the Teacher Efficacy for Inclusive Practices Scale to measure teacher efficacy. The results of the showed upper-middle level scores for both attitudes (3.15 points of 5) and efficacy (3.17 points of 5) in participating pre-service teachers with a statistically significant positive correlation between attitude and efficacy. Implications and future directions for providing adequate training to pre-service general educators to promote inclusive education for students with disabilities are also discussed.